2020
DOI: 10.1016/j.pdpdt.2020.101808
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial photodynamic therapy compared to systemic antibiotic therapy in non-surgical treatment of periodontitis: Systematic review and meta-analysis

Abstract: Background: Periodontitis is one of the most prevalent inflammatory diseases in humans. It is associated with the presence of bacteria and is mediated by the host's immune response This study represents a systematic review and meta-analysis trying to answer the following question: "What is the effect of antimicrobial photodynamic therapy (aPDT) as an adjunct to scaling and root planing (SRP) compared to systemic antibiotic therapy with amoxicillin plus metronidazole (AMX+MTZ) on the non-surgical treatment of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 36 publications
(120 reference statements)
1
21
0
Order By: Relevance
“…Whether aPTD is more effective than antibiotics as an adjunct to scaling and root planning is still debatable [56]. In a meta-analysis study, Souza et al compared aPDT with systemic antibiotic use as adjuncts to SRP, and found similar improvement in the clinical status for both proposed treatments [57]. A 2019 systematic review analyzed whether SRP plus antimicrobial photodynamic therapy exerted an improved clinical outcome in comparison to SRP plus systemic antibiotics in periodontal disease.…”
Section: Antibiotics Vs Antimicrobial Photodynamic Therapy (Apdt)mentioning
confidence: 99%
“…Whether aPTD is more effective than antibiotics as an adjunct to scaling and root planning is still debatable [56]. In a meta-analysis study, Souza et al compared aPDT with systemic antibiotic use as adjuncts to SRP, and found similar improvement in the clinical status for both proposed treatments [57]. A 2019 systematic review analyzed whether SRP plus antimicrobial photodynamic therapy exerted an improved clinical outcome in comparison to SRP plus systemic antibiotics in periodontal disease.…”
Section: Antibiotics Vs Antimicrobial Photodynamic Therapy (Apdt)mentioning
confidence: 99%
“…PDT can be applied for disinfection and sterilization [4][5][6][7]. Microbial, including bacterium and viruses can be removed by photosensitized reaction.…”
Section: Electron Transfer Mechanism and Antimicrobial Photodynamic Tmentioning
confidence: 99%
“…This treatment is a medicinal application of photochemistry. Antimicrobial treatment, called as antimicrobial photodynamic therapy (aPDT) or photodynamic antimicrobial chemotherapy (PACT), is also important application [4][5][6][7]. In the case of cancer treatment, less-toxic PDT reagents, photosensitizers, cause oxidative damage to biomolecules, including protein, nucleic acids, and/or other compounds, under visible-light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…PDT that targets bacteria in particular is called antimicrobial photodynamic therapy (a-PDT). These therapies are beginning to be used to eliminate bacterial infections in periodontal disease [3][4][5][6], infected root canal treatment [7][8][9][10], and caries treatment [11][12][13][14]. There are three elements required for a-PDT: a photosensitizer, an excitation light, and oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there was no statistical difference in the clinical parameters between the group treated with SRP under systemic antibiotics and the group treated with a-PDT and SRP [3] or patients with periodontitis. There was no statistical difference in probing depth (PD) and clinical attachment level (CAL) when conventional periodontal therapy (SRP) and a-PDT were compared in patients with peri-implantitis [5]. In addition to these studies, the effects of a-PDT on antibacterial and inflammatory cytokines have been investigated.…”
Section: Introductionmentioning
confidence: 99%